Ironia w literaturze sowizdrzalskiej - Maciejczyk, Ewa (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
The article illustrates ways of perceiving irony in Old Polish literature, especially in the Owlglass literature created between 16th and 17th century in Poland. The main goal of this work is to analyse fragments of texts classified into three groups connected with three genres of literature: drama, epic and lyrics. It is crucial not only to analyze them, but also to indicate various ways of creating ironic announcements and to reveal the difference between irony and comedy. Moreover, it is important to know whether this irony is a carrier of comedy or if it can exist independently next to comedy. Therefore, it is vital to show how the 16th century reality influenced the authors of Owlglass literature and whether it had any impact on their literature and was mirrored by the irony targeting politics, priests and burghers.